2022
DOI: 10.3390/cells11020180
|View full text |Cite
|
Sign up to set email alerts
|

T and NK Cell-Based Immunotherapy in Chronic Viral Hepatitis and Hepatocellular Carcinoma

Abstract: In chronic viral hepatitis and in hepatocarcinoma (HCC), antigen-specific T cells are deeply exhausted, and evidence of dysfunction has also been observed for NK cells, which can play a pathogenetic role, exerting a regulatory activity on adaptive immune responses [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…M2 macrophages play an important role in the formation of an immunosuppressive microenvironment [ 46 ]. Notably, NK cells showed dysfunction in HCC [ 47 ], but we found that G6PD was associated with KIR2DL4, a marker of NK cells. Recent studies have found that blocking the binding of KIR2DL4 to the ligand on NK cells can restore the sensitivity of breast cancer to trastuzumab [ 48 ].…”
Section: Discussionmentioning
confidence: 86%
“…M2 macrophages play an important role in the formation of an immunosuppressive microenvironment [ 46 ]. Notably, NK cells showed dysfunction in HCC [ 47 ], but we found that G6PD was associated with KIR2DL4, a marker of NK cells. Recent studies have found that blocking the binding of KIR2DL4 to the ligand on NK cells can restore the sensitivity of breast cancer to trastuzumab [ 48 ].…”
Section: Discussionmentioning
confidence: 86%
“…Due to the importance to human health, the current success of cell therapy is mainly based on the use of immune cells, especially T cells, as the chassis therapeutic cells. More recently, other immune cells, such as natural killer cells, macrophages, have shown considerable potential not only in cancer treatment but also in treating infectious diseases (Fisicaro and Boni, 2022;Klichinsky et al, 2020). While many cells being engineered as drugs are still at proof-ofconcept , we envision that once we can design more accurate and functional gene and cellular circuits, engineering at the primary cell level will be easier.…”
Section: Engineered Living Cell Therapeuticsmentioning
confidence: 99%
“…such as: lung cancer [7], hematological tumors [8,9],glioblastoma [10], pancreatic cancer [11],breast cancer [12]and so on. Recent studies have also claimed that NK cells are extremely correlated with HCC, with a decrease in NK cells numbers leading to rapid growth of liver cancer cells and that the poor prognosis of HCC patients is closely linked to failure of cells failure [13][14][15].Thus, it appears that NK cells play the pivotal role in HCC [16]. However, due to some potential biases in studies, such as confounding factors or reverse causation, whether there is a causal correlation between NK cell-associated immune traits and development of HCC remains to be further con rmed and systematically studied.…”
Section: Introductionmentioning
confidence: 99%